INTERGENERATIONAL ALLIANCES IN COMBATING THE CISHETEROPATRIARCHAL CENSORSHIPS - Rocha, Kesia dos Anjos; Oliveira, erika Cecilia Soares [UNESP] (Univ Estado Rio De Janeiro, 2024)
In this writing, the children's literature works Julian is a mermaid and Julian at the wedding by Jessica Love are mobilized as political-artistic and methodological technologies that help us to imagine worlds, childhoods and educational practices that point in the direction of inventiveness, freedom and alterity. The categories childhood and old age, through the characters created by the authoress, guide us in the design of routes that destabilize those normative structures. Throughout the text, we problematize the recent movements to censor children's books in the national and international context, seeking to understand how these movements come about, what influences them and what are the main arguments used by groups that undertake these censorship actions to justify them. Secondly, our efforts are directed towards defending educational processes that are not aimed at maintaining the norm, but rather at encouraging freedom of choice and guaranteeing access to information, which is understood as a right. The discussions undertaken allow us to conclude that there is an erasure of the bodies and perspectives of girls and boys with regard to their experimentation, play and access to information. To protect the childhoods is the great preoccupation of the educational agents and the silences and the surveillances are present in the quotidian doings and thoughts.
Keywords: Childhoods; Old ages; Infant-juvenile literature; Censorships; J & eacute;ssica Love